Adolescents’ Reproductive Health Knowledge and Risky Sexual Behavior: A Correlational Study - Aprilia, Mitha; Handayani, Siti; Mulyanti, Sri (Poltekkes Kemenkes Surakarta, 2023)
Background: Many teenagers engage in underage dating involving sexual activity, as well as unhealthy behaviors such as smoking, alcohol consumption, and drug use. Early prevention through counseling and education on reproductive health and risky sexual behavior is essential. To identify the relationship between reproductive health knowledge and risky sexual behavior among adolescents. Methods: Analytical observational method with a crosssectional approach. The sampling technique used, namely purposive sampling of 69 respondents. This research instrument uses a questionnaire sheet. Statistical tests using the Spearman Rank test. Results: The Spearman Rank correlation coefficient was 0.307, indicating a positive relationship between reproductive health knowledge and risky sexual behavior. Conclusion: There is a positive correlation between reproductive health knowledge and risky sexual behavior in adolescents. Educational programs are recommended to improve awareness and reduce risky behavior.